2009
DOI: 10.2131/jts.34.469
|View full text |Cite
|
Sign up to set email alerts
|

Low dose effects of dichlorodiphenyltrichloroethane (DDT) on gene transcription and DNA methylation in the hypothalamus of young male rats: implication of hormesis-like effects

Abstract: -To verify the relationship between oxidative stress and DNA methylation in the young brain, dichlorodiphenyltrichloroethane (DDT) was administered by gavage to male young rats at doses of 0, 0.006, 0.06, 0.6, 6, and 60 mg/kg/day for a period of 4 weeks. The most conspicuous decrease in the lipid peroxidation level was observed in the 0.06 mg/kg/day group compared with controls. Microarray analysis of brain samples from the control and 0.06 mg/kg/day groups revealed that the expression of 40 genes was changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 53 publications
2
30
0
1
Order By: Relevance
“…Another example are OCs. A Japanese study demonstrated that a low dose of DDT exposure in rats affected DNA methylation in the hypothalamus 39. The assumption, that changes in gene expression related to DDE and PCB as reported in this paper are epigenetic, is also supported by findings that global DNA hypomethylation in Grandlandic Inuits is related to their DDE and PCB burden 40.…”
Section: Discussionsupporting
confidence: 65%
“…Another example are OCs. A Japanese study demonstrated that a low dose of DDT exposure in rats affected DNA methylation in the hypothalamus 39. The assumption, that changes in gene expression related to DDE and PCB as reported in this paper are epigenetic, is also supported by findings that global DNA hypomethylation in Grandlandic Inuits is related to their DDE and PCB burden 40.…”
Section: Discussionsupporting
confidence: 65%
“…A recent study of an elderly white population (N = 524) in Sweden observed that high serum levels of PCB126, OCDD, and p,p′-DDE as well as high toxic equivalence quotient (TEQ) were related to global DNA hypermethylation using the Luminometric Methylation Assay, which is based on restriction enzymes (Lind et al 2013 ). Exposure to DDT altered the methylation pattern in the hypothalamus of young male rats, as found in a study which indicated that six CpG islands in Sst , Gal , Arf1 , Ttr , Msx1 , and Grifi n genes were signifi cantly hypomethylated compared with controls (Shutoh et al 2009 ). A mixture of organochlorine pesticides, PCBs, and methylmercury chloride administered to pre-pubertal female Sprague-Dawley rats resulted in reduced hepatic global genome DNA methylation as well as in particular CpG sites in the tumor suppressor p16 INK4a promoter (Desaulniers et al 2009 ).…”
Section: Endocrine Disruptorssupporting
confidence: 53%
“…A mixture of organochlorine pesticides, PCBs, and methylmercury chloride administered to pre-pubertal female Sprague-Dawley rats resulted in reduced hepatic global genome DNA methylation as well as in particular CpG sites in the tumor suppressor p16 INK4a promoter (Desaulniers et al 2009 ). The mechanisms underlying the process of altered methylation from POPs exposures is still unclear, and it has been suggested that low levels of oxidative stress appear to correlate positively with hypomethylation (Shutoh et al 2009 ).…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
“…Of note are the findings that low doses of DDT reduce the expression of the Dnmt1 gene in the hypothalamus of young male rats, a process correlating with global hypomethylation and demethylation of CpG islands (Shutoh et al 2009). Similar observations of global hypomethylation by DDT are also found in Greenlandic Inuit populations, as discussed in the aforementioned case for PCB exposure (Rusiecki et al 2008).…”
Section: Ddt and Ddementioning
confidence: 99%